2021
DOI: 10.3389/fonc.2021.630921
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV and Saponins of Rhizoma Polygonati Cure Cyclophosphamide-Induced Myelosuppression in Lung Adenocarcinoma via Down-Regulating miR-142-3p

Abstract: Our previous study revealed that Shuanghuang Shengbai granule could cure the myelosuppression induced by cyclophosphamide (CTX) in lung cancer. However, its hematopoietic effects and molecular mechanisms remain not fully understood. Therefore, this study was intended to investigate the effects and the underlying mechanisms of Astragaloside IV (AS) and saponins of rhizoma polygonati (SRP), the two main bioactive ingredients of Shuanghuang Shengbai granule, on CTX-induced myelosuppression. CTX inhibited the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Pharmacologically, Polygonati Rhizoma has diverse therapeutic actions, including anti-oxidant, anti-diabetic, anti-osteoporosis, anti-cancer, anti-microbial, anti-hyperlipidemic, cardiomyocyte protection, immunomodulatory function, effects against infertility, and enhancement of sleep and memory. [17192021]…”
Section: Summary Of the Precious Chinese Medicines Included In This S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacologically, Polygonati Rhizoma has diverse therapeutic actions, including anti-oxidant, anti-diabetic, anti-osteoporosis, anti-cancer, anti-microbial, anti-hyperlipidemic, cardiomyocyte protection, immunomodulatory function, effects against infertility, and enhancement of sleep and memory. [17192021]…”
Section: Summary Of the Precious Chinese Medicines Included In This S...mentioning
confidence: 99%
“…Pharmacologically, Polygonati Rhizoma has diverse therapeutic actions, including anti-oxidant, anti-diabetic, anti-osteoporosis, anti-cancer, anti-microbial, anti-hyperlipidemic, cardiomyocyte protection, immunomodulatory function, effects against infertility, and enhancement of sleep and memory. [17,[19][20][21] Astragalus membranaceus (A. membranaceus) is a major tonic used in TCM practice. The medicinal use of this herb was first recorded in the Shen Nong Ben Cao Jing (《神农本 草经》Shennong's Classic of Materia Medica), which was written approximately 2000 years ago.…”
Section: Summary Of the Precious Chinese Medicines Included In This S...mentioning
confidence: 99%
“…At the same time, it treats osteoporosis, diabetes, and lung disease. [3][4][5] Scutellaria baicalensis (SB) is a traditional Chinese medicine (TCM) widely used in clinical practice. According to "Shennong's Classic of Materia Medica," it is an herb of the genus Scutellaria and is used as a medicine by its roots.…”
Section: Introductionmentioning
confidence: 99%
“…Polygonatum Rhizoma (PR) is a perennial herb of the genus, first published in the ancient Chinese book “The Book of Famous Doctors.” 2 It is mainly for lung‐dryness with nonproductive cough and body deficiency. At the same time, it treats osteoporosis, diabetes, and lung disease 3–5 . Scutellaria baicalensis (SB) is a traditional Chinese medicine (TCM) widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Current drugs promoting the recovery of BMHSC functions, such as erythropoietin and thrombopoietin, are expensive, while a recombinant colony-stimulating factor can potentially stimulate tumor cell proliferation. Gu et al, (2021) tested the anti-myelosuppressive efficacy of the main bioactive components of traditional Chinese medicine Shuanghuang Shengbai granule in a mouse model of cyclophosphamide (CTX)-treated lung adenocarcinoma. The study demonstrated that these bioactive components improve the hematopoietic function of BMHSCs via upregulation of high mobility group box 1 protein through inhibition of miR-142-3p, which alleviates CTX-induced cell injury and myelosuppression in this model.…”
mentioning
confidence: 99%